Two magnetic sensor based real-time tracking of magnetically inflated swallowable intragastric balloon - Miyasaka, Muneaki (2022)
This paper presents a two magnetic sensor based tracking method for a magnetically inflated intragastric balloon capsule (MIBC) which is used for obesity treatment. After the MIBC is swallowed, it is designed to be inflated inside the stomach by approaching a permanent magnet (PM) externally near the abdomen. However, if the balloon inflation is accidentally triggered while the MIBC is still in the esophagus, the esophagus will be damaged. Therefore, to safely inflate the MIBC, we aim to track the MIBC's position along the esophagus and confirm the MIBC passes through. Typically, magnetic sensor based tracking systems tend to be bulky and costly since they involve computationally intensive optimization with many magnetic sensors. To solve those problems, we develop an algorithm that estimates the position of the PM inside the MIBC by using the grid search combined with the dynamically confined search range and search threshold modulation. Our tracking method achieved an average 1D position error of 3.48 mm which is comparable to the up to 4 mm average error for the other magnetic sensor based tracking systems that require more sensors and computational power compared to our system.